2020
DOI: 10.3390/nu12072016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Weight and Nutritional Habits in Adults with Obesity during the “Lockdown” Period Caused by the COVID-19 Virus Emergency

Abstract: Our aim is evaluating the changes in weight and dietary habits in a sample of outpatients with obesity after 1 month of enforced lockdown during the COVID-19 pandemic in Northern Italy. In this observational retrospective study, the patients of our Obesity Unit were invited to answer to a 12-question multiple-choice questionnaire relative to weight changes, working activity, exercise, dietary habits, and conditions potentially impacting on nutritional choices. A multivariate regression analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
545
12
30

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(652 citation statements)
references
References 27 publications
65
545
12
30
Order By: Relevance
“…Through analyzing the difference of four groups (underweight, normal weight, overweight and obesity) in BMI change and weight change before and during the home con nement, we found unexpectedly that participants of normal weight gained more weight than obese objects, resulting from small samples in obese group (n = 19). Likewise, our survey indicated that self-reported depression was related to gain weight, which coincided with the previous study (6).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Through analyzing the difference of four groups (underweight, normal weight, overweight and obesity) in BMI change and weight change before and during the home con nement, we found unexpectedly that participants of normal weight gained more weight than obese objects, resulting from small samples in obese group (n = 19). Likewise, our survey indicated that self-reported depression was related to gain weight, which coincided with the previous study (6).…”
Section: Discussionsupporting
confidence: 91%
“…However, emotional and lifestyle changes during self-quarantine might increase the risks of obesity during quarantine (2)(3)(4). Home con nement for several months could lead to weight gain, further increasing incidence of obesity (5).To many patients in Italy, weight gain was found related to increased self-reported anxiety or depression and not consuming healthy food in obese adults according to multiple regression analysis (6). In Poland, almost 30% of people gain weight of 3.0 ± 1.6 kg, and it seemed that overweight, obese and older individuals were more likely to gain weight (7).…”
Section: Introductionmentioning
confidence: 99%
“…A similar cross-sectional observation on a larger sample size, including subjects aged more than 12 years old belonging to every region, reported an increased egg, meat, and pulse consumption by up to 15% [ 14 ]. Similarly, the majority (81%) of the overweight Italians surveyed by Pellegrino et al [ 16 ] showed equal or greater consumption of overall protein sources than pre-COVID-19. Again, a quarter of the 700 Chilean investigated by Reyes-Olavarría et al declared that they consumed red and white meat more than 3 times/week [ 20 ].…”
Section: Resultsmentioning
confidence: 93%
“…In this regard, the only longitudinal observation, carried out by Ghosh et al on a fairly small Indian sample, revealed a 21% increase in the daily consumption of grains and rice [ 13 ]. Similarly, seven cross-sectional observations showed that a large majority consumed higher amounts of cereals [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In particular, homemade pizza, fresh bread, pasta, and rice were found to rule the trend among the Italian and Spanish surveys performed over a wide range of ages and sample sizes (increases by up to 40% and 39%, respectively) [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…These strategies can diminish the effects and over time (in part) counteract the negative consequences of the lockdown. Unfortunately, the lockdowns and related increase in anxiety, depression, and PTSD ( Guessoum et al, 2020 ), and as many sports facilities were closed this related to changes in life style such as eating more, and sporting less ( Di Renzo et al, 2020 ; Górnicka et al, 2020 ; Pellegrini et al, 2020 ). Paradoxically, functional coping styles in order to offset some of these negative effects have been blocked in some ways due to the measures and this may have led to downward spirals in terms of (mental) health ( Ibrahimagić et al, 2020 ).…”
Section: Coping Styles Can Alleviate or Exacerbate Some Of The Side Ementioning
confidence: 99%